Nie tylko reklama. Artystyczny status zwiastuna filmowego (w kontekście Psychozy Alfreda Hitchcocka) - Górny, Anna (Załącznik Kulturoznawczy, 2020)
Film trailers are usually dismissed as supplements to artistic texts which are the films themselves. Their ‘fleeting’ status reinforces the belief that a trailer is only meant to pave the way for the fully-fledged work. Trailers are of course a form of advertising, but at the same time they constitute short audiovisual works that can also be judged in artistic terms. This article is an attempt to demonstrate that the character of the trailers produced by director Alfred Hitchcock is expressed not only in the creation of spectacular short forms of advertising, signed by the author’s brand of the ‘master of suspense’, but also in opening up a new field of research on the trailers themselves - as small audiovisual forms whose relation to the main text does not have to be at all simple or unambiguous - and in blazing new trails in their development. The trailer to Psycho (1960), which in itself is an artistically interesting statement, described in the article as a case study, reveals the elements that most fully present this director’s approach to promotional texts. Different from a typical commercial, it can be seen in the context of the auteur theory, and perhaps also illustrates some of Gilles Deleuze’s or David Bordwell’s claims, which helps to place this ephemeral film form in a broader film discourse.